(untitled) (Research, Society and Development, 2024)
The term postoperative nausea and vomiting (PONV) is commonly used to describe nausea and/or vomiting in the post-anesthesia recovery room (PACU) or within the immediate 24-hour postoperative period. It is characterized as a multifactorial adverse response to anesthesia and surgical operation that is feared by patients, usually classified as worse than postoperative pain. This study aimed to provide the most up-to-date information regarding the pathophysiology, risk factors, prophylaxis, and treatment of PONV, based on scientific evidence and the latest guidelines. The presented research refers to a narrative review of the literature. Searches were conducted in journals indexed in the PubMed, LILACS, and SciELO databases. Additionally, a search was made in books of significant importance in the field of Anesthesiology. Although not yet fully elucidated, some pathophysiological pathways of PONV are already well described. Regarding risk factors, the literature establishes some factors such as female sex, non-smoker status, history of PONV, and opioid use in surgery, in addition to other factors that are discussed. Prophylaxis and treatment are based on the guideline released in 2020 by Gan and colleagues. PONV carries a negative impact on patient well-being. Thus, PONV constitutes a complication with high impact and prevalence, despite advances in science regarding the topic. It is the physician’s role to be aware of the risks in order to avoid such complication.